Lao PDR Economic Monitor, June 2020 : Lao PDR in the Time of COVID-19 - World Bank (World Bank, Vientiane, 2020)
Lao People’s Democratic Republic (PDR) has so far avoided a major health crisis but has not been immune from the global economic downturn. The COVID-19 (Coronavirus) induced economic downturn has affected Lao PDR through multiple channels including tourism, trade, investment, commodity prices, exchange rates, and lower remittances. This report presents a range of growth estimates for 2020 under two scenarios. These scenarios reflect different assumptions regarding: (i) the duration and depth of outbreaks and lockdown in Lao PDR, (ii) the magnitude and effectiveness of economic relief policies, and (iii) the depth and duration of the global downturn. The COVID-19 shock has further aggravated the long-standing structural vulnerabilities in the economy. The country has a legacy of weak macroeconomic management, resulting in limited fiscal and foreign currency buffers even before the global pandemic. Limited fiscal space and the mounting pressure of deficit financing and debt servicing will limit the ability of the Government of Lao PDR (GoL) to stimulate the economy, exacerbating the downturn.